enter image description here


I want to know the proof omitted. Please, help me.


3 Answers 3


I don't think this question is a better fit on math.SE as Xi'an avers (actually dsp.SE might be a better fit where a lot of digital communications systems questions seem to end up) nor do I agree that it is off-topic here. I don't have a complete answer for the OP but nonetheless, here goes.

Let $[Y_1, Y_2] = [H_1, H_2] + [N_1, N_2]$ where the $H_i$ are i.i.d. $N(0,\sigma_h^2)$ and the $N_i$ are i.i.d. $N(0,\sigma_n^2)$, and the $H$'s and $N$'s are also mutually independent (the OP does not state this but I think it is implicit in the model). Then, it is easily seen that the $Y_i$ are i.i.d. $N(0,\sigma_h^2 + \sigma_n^2)$ random variables.

As background, in a digital communications systems context, $[H_1, H_2]$ is the measurement of the two components of a Rayleigh faded signal $\big($the signal amplitude $\sqrt{H_1^2+H_2^2}$ is a Rayleigh random variable$\big)$ received in Gaussian noise (which results in the actual measurement $$[Y_1, Y_2] = [H_1, H_2] + [N_1, N_2],$$ where $[N_1,N_2]$ is the Gaussian noise in the measurement of the two components). The question thus is to find the conditional distribution of the signal energy $\mathscr{E}_h = H_1^2+H_2^2$ given the value of the received energy $\mathscr{E}_y = Y_1^2+Y_2^2$. Note that both $\mathscr{E}_h$ and $\mathscr{E}_y$ are exponential random variables.

Now, in the digital communications literature, the distribution of $\sqrt{X^2+Y^2}$ where $X$ and $Y$ are independent Gaussian random variables with nonzero means $\alpha_1$ and $\alpha_2$ and common variance $\sigma^2$ is called the Ricean distribution (after S.O. Rice, "Mathematical Analysis of Random Noise," Bell System Technical Journal, 1944, 1945) whose density is $$f_{\sqrt{X^2+Y^2}}(u) = \frac{u}{\sigma^2}\exp\left(-\frac{u^2+\alpha_1^2+\alpha_2^2}{2\sigma^2}\right)I_0\left(\frac{u\sqrt{\alpha_1^2+\alpha_2^2}}{\sigma^2}\right), ~u \geq 0.\tag{1}$$ It follows that the density of $X^2+Y^2$ is given by \begin{align}f_{X^2+Y^2}(v) &= \frac{1}{\sqrt{v}}f_{\sqrt{X^2+Y^2}}(\sqrt{v})\\ &= \frac{1}{\sigma^2}\exp\left(-\frac{v+\alpha_1^2+\alpha_2^2}{2\sigma^2}\right)I_0\left(\frac{\sqrt{v(\alpha_1^2+\alpha_2^2)}}{\sigma^2}\right), ~v \geq 0.\tag{2}\end{align}

We use the results in $(1)$ and $(2)$ to attain the desired result as follows. For $i=1,2$, $Y_i$ and $H_i$ are zero-mean jointly normal random variables with respective variances $\sigma_h^2 + \sigma_n^2$ and $\sigma_h^2$ and covariance $\sigma_h^2$. Hence, conditioned on $Y_i=\alpha_i$, the conditional distribution of $H_i$ is normal with mean $\frac{\sigma_h^2}{\sigma_h^2 + \sigma_n^2}\alpha_i$ and variance $\frac{\sigma_h^2\sigma_n^2}{\sigma_h^2+\sigma_n^2}$. Note that the variance does not depend on the value of $\alpha_i$. Furthermore, since $[Y_1,H_1]$ is independent or $[Y_1.H_2]$, then conditioned on $[Y_1,Y_2] = [\alpha_1, \alpha_2]$, the random variables $H_1$ and $H_2$ are independent normal random variables with means as specified above and common variance $\frac{\sigma_h^2\sigma_n^2}{\sigma_h^2+\sigma_n^2}$. Thus, we can use $(2)$ to write down that for $v \geq 0$, $$f_{\mathscr{E}_h \mid [Y_1,Y_2] = [\alpha_1, \alpha_2]}(v\mid\alpha_1, \alpha_2) \\= \frac{\sigma_h^2+\sigma_n^2}{\sigma_h^2\sigma_n^2} \exp\left(-\frac{\sigma_h^2+\sigma_n^2}{2\sigma_h^2\sigma_n^2}v\right) \exp\left(-\frac{\sigma_h^2}{2\sigma_n^2(\sigma_h^2+\sigma_n^2)}(\alpha_1^2+\alpha_2^2)\right) I_0\left(\frac{\sqrt{v(\alpha_1^2+\alpha_2^2)}}{\sigma_n^2}\right).~~(3)$$ But what if instead of knowledge of the values $\alpha_1$ and $\alpha_2$ of $Y_1$ and $Y_2$ separately, we only know the value of $Y_1^2+Y_2^2$, that is, the value $E_y$ of the random variably $\mathscr{E}_y$? Well, as $(3)$ shows, we don't really need the values of $\alpha_1$ and $\alpha_2$, and we have that $$f_{\mathscr{E}_h \mid \mathscr{E}_y = E_y}(v\mid E_y) \\= \frac{\sigma_h^2+\sigma_n^2}{\sigma_h^2\sigma_n^2} \exp\left(-\frac{\sigma_h^2+\sigma_n^2}{2\sigma_h^2\sigma_n^2}v\right) \exp\left(-\frac{\sigma_h^2}{2\sigma_n^2(\sigma_h^2+\sigma_n^2)}E_y\right) I_0\left(\frac{\sqrt{vE_y}}{\sigma_n^2}\right), v \geq 0.~~(4)$$ Replacing $\sigma_h^2$ and $\sigma_n^2$ by $\frac{\lambda}{2}$ and $\frac{\mu}{2}$ respectively, we get the pdf $$f_{\mathscr{E}_h \mid \mathscr{E}_y = E_y}(v\mid E_y) = \frac{\lambda+\mu}{\lambda\mu} \exp\left(-\frac{\lambda+\mu}{\lambda\mu}v\right) \exp\left(-\frac{\lambda}{\mu(\lambda+\mu)}E_y\right) I_0\left(\frac{2}{\mu}\sqrt{vE_y}\right), v \geq 0.\tag{5}$$

exhibited in the paper that the OP is reading.

  • $\begingroup$ Thank you so much.I knew you could look at the problem from the perspective you mentioned. $\endgroup$
    – W W W
    Jan 18, 2019 at 5:20
  • $\begingroup$ how to derive the expectation and variance? how to deal with Bessel function, deriving the expectation and variance? $\endgroup$
    – W W W
    Jan 28, 2019 at 12:50

A brief description of the derivation below:

  • find the distribution of $H$ conditional on $y$ (using Bayes rule)
  • transform the density to be expressed in coordinates $\varrho_h$ and $\theta$
  • then integrate over the region where $\varrho_h$ is constant, ie a circle (resulting into that Bessel function).

Distribution of $H$ conditional on $y$

The individual distributions are:

$$\begin{array}{rcl} f_Y(y) & = & \frac{1}{\pi (\lambda+\mu)} e^{-(\lambda + \mu)^{-1}\vert y \vert^2} \\ f_H(h) & = & \frac{1}{\pi \lambda} e^{-\lambda^{-1}\vert h \vert^2} \\ f_N(n) & = & \frac{1}{\pi \mu} e^{-\mu^{-1}\vert n \vert^2} \end{array}$$

From which you can derive a conditional distribution (the last step uses the law of cosines):

$$\begin{array}{rcl} f_{H \vert Y}(h \vert y) &=& \frac{f_{Y \vert H}(y \vert h) f_H(h) }{f_Y(y)} \\ & = & \frac{f_{N}(y - h) f_H(h) }{f_Y(y)} \\ & = & \pi^{-1} \frac{\lambda + \mu}{\lambda \mu} \, e^{-\lambda^{-1}\vert h \vert^2} \, e^{(\lambda + \mu)^{-1}\vert y \vert^2} \, e^{-\mu^{-1}\vert y-h \vert^2} \\ & = & \pi^{-1} \frac{\lambda + \mu}{\lambda \mu} \, e^{-\frac{\lambda+\mu}{\lambda \mu}\vert h \vert^2} \, e^{-\frac{\lambda}{\mu (\lambda+\mu)}\vert y \vert^2} \, e^{\frac{2}{\mu} \vert y \vert \vert h \vert cos(\theta)}\\ \end{array}$$

where $\theta$ is the angle between $h$ and $y$.

Coordinate transformation

Note: the density above is for the complex number expressed by Cartesian coordinates ($dx$ and $dy$), we will later use some sort of polar coordinates ($d \theta$ and $d(r^2)$ or $d(\varrho_h)$). The density will transform due to the transformation of the differential element $$dA = dxdy = r drd\theta = 0.5 d(r^2)d\theta = 0.5 d\varrho_h d\theta$$

In polar coordinates $\theta$ and $r$ you get:

$$\begin{array}{rcl} f_{H \vert Y}(h \vert y) &=& r \pi^{-1} \frac{\lambda + \mu}{\lambda \mu} \, e^{-\frac{\lambda+\mu}{\lambda \mu}r^2} \, e^{-\frac{\lambda}{\mu (\lambda+\mu)}\varrho_y} \, e^{\frac{2}{\mu} \sqrt{r^2 \varrho_y}cos(\theta)}\\ \end{array}$$

In coordinates $\theta$ and $\varrho_h = r^2$ you get:

$$\begin{array}{rcl} f_{H \vert Y}(h \vert y) &=& 0.5 \pi^{-1} \frac{\lambda + \mu}{\lambda \mu} \, e^{-\frac{\lambda+\mu}{\lambda \mu}\varrho_h} \, e^{-\frac{\lambda}{\mu (\lambda+\mu)}\varrho_y} \, e^{\frac{2}{\mu} \sqrt{\varrho_h \varrho_y} cos(\theta) }\\ \end{array}$$

Integration to get from '$H$ conditional on $y$' to '$\varrho_H$ conditional on $y$'

If you integrate this for $0 \leq \theta< 2\pi$ you get$^\dagger$:

$$\begin{array}{rcl} f_{\varrho_H = \varrho_h \vert \varrho_Y}(\varrho_h \vert \varrho_y) &=& f_{\varrho_H = \varrho_h \vert Y}(\varrho_h \vert y) \\ &=& \int_0^{2\pi} f_{H \vert Y}(h \vert y) d\theta \\ &=& \frac{\lambda + \mu}{\lambda \mu} \, e^{-\frac{\lambda+\mu}{\lambda \mu}\varrho_h} \, e^{-\frac{\lambda}{\mu (\lambda+\mu)}\varrho_y} \, I_0\left(\frac{2}{\mu} \sqrt{\varrho_h \varrho_y} \right)\\ \end{array}$$

using the property $\int_0^{2\pi} e^{x \cos(\theta)}d\theta = 2\pi I_0(x)$ and noting that $f_{\varrho_H = \varrho_h \vert \varrho_Y}(\varrho_h \vert \varrho_y) = f_{\varrho_H = \varrho_h \vert Y}(\varrho_h \vert y)$ for any $y$ due to the spherical symmetry.

Finding raw moments

In order to find the $k$-th raw moment you would have to integrate

$$\int \varrho_h^k f(\varrho_h) d \varrho_h$$

or replacing $\varrho_h$ by $z^2$ $$\int z^{2k+1} f(z^2) d z$$

which is basically (up to some constant) an integral of the form

$$\int z^{2k+1} e^{-z^2} I_0(a z) dz$$

(I have for the moment no solution for that)

$\dagger$ this is a bit direct. You could also first integrate over the disk (angle and radius), instead of over the circle, to get something like $P(\varrho_H<x|\varrho_Y)$, which is the cdf, and then differentiate over $x$ to get the pdf.

  • $\begingroup$ Thank you so much. It has helped too much. I learned a lot from you. $\endgroup$
    – W W W
    Jan 18, 2019 at 5:18
  • $\begingroup$ how to derive the expectation and variance? how to deal with Bessel function, deriving the expectation and variance? $\endgroup$
    – W W W
    Jan 28, 2019 at 12:50

Cumulant generating function: The density has an exponential term in it, so finding the moment generating function is pretty simple. First we define the transformed parameter:

$$\lambda' \equiv \frac{\lambda}{1-t \lambda} \quad \quad \quad \iff \quad \quad \quad \frac{\lambda+\mu}{\lambda \mu} - t = \frac{\lambda'+\mu}{\lambda' \mu}.$$

With a bit of algebra, we then have:

$$\begin{equation} \begin{aligned} m(t) \equiv \mathbb{E} [ e^{t \varrho_h} | \varrho_y ] &= \int \limits_0^\infty e^{t \varrho_h} f(\varrho_h|\varrho_y) \ d\varrho_h \\[6pt] &= \int \limits_0^\infty \frac{\lambda + \mu}{\lambda \mu} e^{- \varrho_h \Big( \tfrac{\lambda + \mu}{\lambda \mu} - t \Big)} e^{- \varrho_y \Big( \tfrac{\lambda}{\mu (\lambda + \mu)} \Big)} I_0 \Big( \frac{2}{\mu} \sqrt{\varrho_h \varrho_y} \Big) \ d\varrho_h \\[6pt] &= \frac{\lambda + \mu}{\lambda + \mu - t \lambda \mu} \cdot e^{- \varrho_y \Big( \tfrac{\lambda}{\mu (\lambda + \mu)} - \tfrac{\lambda}{\mu (\lambda + \mu (1-t\lambda))} \Big)} \\[6pt] &\quad \times \int \limits_0^\infty \Big( \frac{\lambda + \mu}{\lambda \mu} - t \Big) e^{ - \varrho_h \Big( \tfrac{\lambda + \mu}{\lambda \mu} -t \Big)} e^{- \varrho_y \Big( \tfrac{\lambda}{\mu (\lambda + \mu (1-t\lambda))} \Big) } I_0 \Big( \frac{2}{\mu} \sqrt{\varrho_h \varrho_y} \Big) \ d\varrho_h \\[6pt] &= \frac{\lambda + \mu}{\lambda + \mu - t \lambda \mu} \cdot \exp \Big( \varrho_y \cdot \frac{t \lambda^2}{(\lambda + \mu) (\lambda + \mu (1-t \lambda))} \Big) \\[6pt] &\quad \times \int \limits_0^\infty \frac{\lambda' + \mu}{\lambda' \mu} e^{ - \varrho_h \Big( \tfrac{\lambda' + \mu}{\lambda' \mu} \Big)} e^{- \varrho_y \Big( \tfrac{\lambda'}{\mu (\lambda' + \mu)} \Big) } I_0 \Big( \frac{2}{\mu} \sqrt{\varrho_h \varrho_y} \Big) \ d\varrho_h \\[6pt] &= \frac{\lambda + \mu}{\lambda + \mu - t \lambda \mu} \cdot \exp \Big( \varrho_y \cdot \frac{t \lambda^2}{(\lambda + \mu) (\lambda + \mu (1-t \lambda))} \Big). \\[6pt] \end{aligned} \end{equation}$$

Taking the logarithm gives the cumulant generating function:

$$K(t) \equiv \log m(t) = \log(\lambda + \mu) - \log(\lambda + \mu - t \lambda \mu) + \varrho_y \cdot \frac{t \lambda^2}{(\lambda + \mu) (\lambda + \mu (1-t \lambda))}.$$

Mean: The first derivative of the cumulant generating function is:

$$\frac{dK}{dt}(t) = \frac{\lambda \mu}{\lambda + \mu - t \lambda \mu} + \varrho_y \cdot \frac{\lambda^2}{(\lambda + \mu) (\lambda + \mu (1-t \lambda))} + \varrho_y \cdot \frac{t \mu \lambda^3}{(\lambda + \mu) (\lambda + \mu (1-t \lambda))^2},$$

so we have:

$$\mathbb{E}( \varrho_h | \varrho_y ) = \frac{dK}{dt}(0) = \frac{\lambda \mu}{\lambda + \mu} + \varrho_y \cdot \frac{\lambda^2}{(\lambda + \mu)^2} = \frac{\lambda \mu}{\lambda + \mu} \Bigg( 1 + \varrho_y \cdot \frac{\lambda}{\mu (\lambda + \mu)} \Bigg).$$

Variance: The second derivative of the cumulant generating function is:

$$\begin{equation} \begin{aligned} \frac{d^2 K}{dt^2}(t) &= \Big( \frac{\lambda \mu}{\lambda + \mu - t \lambda \mu} \Big)^2 + \varrho_y \cdot \frac{2 \mu \lambda^3}{(\lambda + \mu) (\lambda + \mu (1-t \lambda))^2} \\[6pt] &\quad + \varrho_y \cdot \frac{t \mu^2 \lambda^4}{(\lambda + \mu) (\lambda + \mu (1-t \lambda))^3}, \end{aligned} \end{equation}$$

so we have:

$$\mathbb{V}( \varrho_h | \varrho_y ) = \frac{d^2 K}{dt^2}(0) = \Big( \frac{\lambda \mu}{\lambda + \mu} \Big)^2 + \varrho_y \cdot \frac{2 \mu \lambda^3}{(\lambda + \mu)^3} = \Big( \frac{\lambda \mu}{\lambda + \mu} \Big)^2 \Bigg( 1 + 2 \varrho_y \cdot \frac{\lambda}{\mu (\lambda + \mu)} \Bigg).$$

  • $\begingroup$ in derivation of moment generating function m(t), how to solve the integral containing Bessel function? As the integrand is pdf, the integral has 1? $\endgroup$
    – W W W
    Mar 2, 2019 at 5:44
  • $\begingroup$ That's correct - integral is the same pdf, but with parameter $\lambda'$ instead of $\lambda$, so it integrates to one. $\endgroup$
    – Ben
    Mar 2, 2019 at 7:35

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.